2012
DOI: 10.1111/j.1574-6941.2011.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Truffle brûlé: an efficient fungal life strategy

Abstract: The terms 'brûlé' and 'burnt' are used to describe vegetation-devoid areas of the ground around a range of woody plants interacting with certain truffle species. Increasing interest is currently focused on a systematic search for and study of volatile organic compounds (VOCs) emitted by truffles in the course of their life cycle. These metabolites are now recognized as biochemicals with an important impact on burnt formation. Based on current molecular approaches, Tuber melanosporum is emerging as an aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
65
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 47 publications
2
65
0
Order By: Relevance
“…Tuber melanosporum was found to be the dominant fungus within the brûlé, where Basidiomycota ectomycorrhizal fungi decreased, indicating a competitive effect of T. melanosporum with the other ectomycorrhizal fungi. have confirmed this fungal dominance by means of 454-pyrosequencing data of the same soils, while Streiblová et al (2012) suggested that truffles adopt an efficient survival strategy by spreading their metabolites, which are regarded as having allelopathic effects on the herbaceous plants and the microorganisms in the rhizosphere. As ectomycorrhizal fungi interact with soil communities to establish a multi-trophic ectomycorrhizal complex ( Frey-Klett et al 2007), Mello et al (2013) compared the bacterial communities between the interior and exterior zones of the brûlé to investigate the potential effects of T. melanosporum growth and metabolites on such communities.…”
Section: Introductionsupporting
confidence: 48%
“…Tuber melanosporum was found to be the dominant fungus within the brûlé, where Basidiomycota ectomycorrhizal fungi decreased, indicating a competitive effect of T. melanosporum with the other ectomycorrhizal fungi. have confirmed this fungal dominance by means of 454-pyrosequencing data of the same soils, while Streiblová et al (2012) suggested that truffles adopt an efficient survival strategy by spreading their metabolites, which are regarded as having allelopathic effects on the herbaceous plants and the microorganisms in the rhizosphere. As ectomycorrhizal fungi interact with soil communities to establish a multi-trophic ectomycorrhizal complex ( Frey-Klett et al 2007), Mello et al (2013) compared the bacterial communities between the interior and exterior zones of the brûlé to investigate the potential effects of T. melanosporum growth and metabolites on such communities.…”
Section: Introductionsupporting
confidence: 48%
“…The hypothesis that T. melanosporum is a dominating colonizer is supported by evidence for a decrease in the overall soil fungal diversity with the development of the truffle brûlé (Napoli et al, 2010). The brûlé is an area nearly barren of plant vegetation surrounding a tree colonized by T. melanosporum and provides a visible indication that T. melanosporum is active in the soil beneath the host tree (Suz et al, 2008;Streiblová et al, 2012). This is an exploratory study to provide 1) a preliminary survey of the diversity of soil fungal communities in truffle plantations with the use of Sanger sequencing before applying more costly and in-depth sequencing methods, and to assess 2) changes in the fungal communities with the advancing succession in truffle plantations established in soils previously dedicated to cereal production.…”
Section: Introductionmentioning
confidence: 81%
“…These compounds recovered from the fungi are low molecular weight molecules, are highly dispensable and are advantageous in various environmental conditions (Gerke and Braus 2014 ). However, the interest in secondary metabolites of symbiotic fungi found in close association with land plants, lichens, marine organisms and insects has recently intensifi ed due to the belief that natural products synthesised by these fungi during ecological interactions exhibited strong biological activities (Keller and Turner 2012 ;Streiblova et al 2012 ;Angelini et al 2015b ).…”
Section: Introductionmentioning
confidence: 97%